Transcriptional trans-activation by the human papillomavirus type 16 E2 gene product. - Phelps, W C (1987)
We identified a conditional transcriptional enhancer in the long control region (LCR) of human papillomavirus type 16 (HPV-16). This conditional enhancer requires activation in trans by a product of the viral early-region open reading frames (ORFs). Primer extension analysis of chloramphenicol acetyltransferase RNA isolated from transiently transfected CV-1 cells demonstrated that trans-activation of the HPV-16 LCR enhancer operated at the transcriptional level. Mutational analysis of the early ORFs demonstrated that the conditional enhancer of the LCR was trans-activated by the product of the E2 ORF. The E2 gene product of bovine papillomavirus type 1, which can trans-activate the conditional enhancer in the bovine papillomavirus type 1 LCR, was also capable of trans-activating the E2-responsive enhancer of HPV-16. The activity of the HPV-16 LCR enhancer was also assayed in two human cervical carcinoma cell lines, HeLa and SiHa, which harbor transcriptionally active, integrated HPV-18 and HPV-16 DNA sequences, respectively. No endogenous E2 or E2-like activity was detected in either cell line.